MMAP-04 CYTOTOXIC, TUMOR-HOMING INDUCED NEURAL STEM CELLS AS AN ADJUVANT TO RADIATION IN THE TREATMENT OF NON-SMALL CELL LUNG CANCER LEPTOMENINGEAL METASTASES. (5th August 2022) - Mercer-Smith, Alison; Jiang, Wulin; Valdivia, Alain; Bell, Noah; Woodell, Alex; Floyd, Scott; Hingtgen, Shawn
Abstract: INTRODUCTION: Non-small cell lung cancer (NSCLC) is the most common cancer to spread to the brain, and spread to the leptomeninges is particularly devastating, with a median survival of only months. While radiation may offer symptomatic relief, new adjuvant therapies are needed for more durable tumor kill. Spheroidal, human induced neural stem cells (hiNeuroS) transdifferentiated from fibroblasts are inherently tumoritropic. When engineered to secrete the cytotoxic protein TRAIL, they provide the potential for a personalized, targeted approach to NSCLC leptomeningeal metastases. METHODS: hiNeuroS-TRAIL in vivo efficacy was determined by tracking the progression and survival of mice with NSCLC leptomeningeal tumors treated with intracerebroventricular hiNeuroS, radiation, or both. To determine the impact of radiation on the tumor tropism of hiNeuroS, we performed 2-dimensional motion assays on hiNeuroS with and without the presence of NSCLC pre- and post-radiation. Migrational capacity in vivo was determined by infusing hiNeuroS into the lateral ventricles of mice with established NSCLC tumors and monitoring hiNeuroS accumulation using post-mortem fluorescent analysis. RESULTS/CONCLUSION: Mice treated with the combination of hiNeuroS-TRAIL and 2 Gy showed a significantly reduced mean tumor signal (2.7%) compared to controls (100%) or 2 Gy-only (54.9%). Mice treated with 2 Gy alone showed no significant survival difference compared to controls. Both combination and hiNeuroS-TRAIL-only-treated mice showed a significant improvement in median survival compared to controls (36.6% and 46.3% improvement, respectively). hiNeuroS showed enhanced directionality and displacement in the presence of NSCLC in 2-dimensional motion assays, indicating directional migration, and they maintained this ability following exposure to radiation. Co-localization of hiNeuroS with NSCLC was also observed in vivo. These results suggest the potential of hiNeuroS-TRAIL as a powerful adjuvant to radiation in the treatment of leptomeningeal NSCLC.